PERILAKU YANG BERHUBUNGAN DENGAN PEDICULOSIS CAPITIS PADA SISWI MADRASAH TSANAWIYAH HIFZIL QUR’AN MEDAN - Salbiah Salbiah (Poltekkes Kemenkes Jakarta III, 2018)
Pediculosis Capitis is an infestation Pediculus humanus var. capitis or commonly known ashead lice on human hair and scalp. The disease had become endemic around the world, bothin developed and developing countries, with most of infestation occurring in school-agechildren. The study aims to know the relationship between behavior with incidence ofPediculosis Capitis on Madrasah Tsanwiyah Hifzil Qur’an Medan students. Type of studyused is analytic study with cross sectional design. Samples amounted to 71 respondents.Sample were drawn by simple random sampling method. Data obtained by way of fillingquestionnaire and hair examination directly. Data then analyzed with chi-square test. Theresult showed that from 71 respondents, 57 respondents (80,3%) had Pediculosis Capitis.The result also showed that there are no relationship between knowledge and attitude withincidence of Pediculosis Capitis (p-value = 0,757 and 0,309). There are relationship betweenaction with incidence of Pediculosis Capitis with p-value = 0,005. The high prevalence ofPediculosis Capitis in these Madrasah Tsanwiyah Hifzil Qur’an Medan students needs to getmore serious treatment. Recomended for students to pay more attention to the things that canhelp spread the Pediculosis Capitis.